Secagem de sementes de soja em leito fixo: equilíbrio e cinética da sílica gel para controle de umidade, modelagem do processo e análise da qualidade das sementes - Souza, Glaucia de Fatima Moreira Vieira e (2013)
The objective of this work was to study the process of drying of soybean seeds in fixed bed, taking into account the heterogeneity of this procedure in this type of dryer and the influence of process variables on the quality of the seed. Also survey was conducted of kinetic and equilibrium isotherms of the silica gel drying order to provide data for a possible use of this material as a means to dehumidify the air to improve the drying process. Was relizada the mathematical simulation of the drying process using the two-step model for verification by experimental data. The equations of Copace and Overhults were considered the most appropriate to represent the equilibrium isotherms and drying kinetics of silica gel, respectively. Through experiments drying of soybean seeds in fixed deep-bed, it was possible to determine seed moisture and temperature of the seeds and drying air along the bed at different axial positions over time, and the quality of seeds at the end of each experiment. It was found that the drying rate increased with temperature and speed, combined with the decrease in relative humidity of the drying air, and in four of the experiments seeds obtained a final moisture content below or near 13-14 % (bs), more favorable conditions for seed quality. The temperature of the seed followed the standard developed by the air temperature along the length of the bed. With respect to mathematical modeling, simulated responses compared with the experimental values showed good agreement, with average deviations ranging from 1.4 to 5.7%. Looking at the quality of the seeds by indices of germination, accelerated aging, sand emergence and seed without cracks after drying can be concluded that in general, increasing the temperature and air velocity combined with the decrease in relative humidity of this air drying affects the quality of the seeds.